Efektifitas Edukasi Manfaat Bunga Telang Terhadap Pengetahuan Ibu Balita Tentang Pencegahan Stunting Menggunakan Media Poster Di Puskesmas Kuta Baro - Lydia Syanesah; Ambia Nurdin; Ully Fitria (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting is one of the chronic nutritional problems that has serious impacts on children’s growth and development. Preventing stunting requires a multisectoral approach, including nutritional education for parents of toddlers. The butterfly pea flower (Clitoria ternatea) is known to contain antioxidants and active compounds beneficial to health and has potential as a local food alternative for preventing stunting. This study aims to analyze changes in parents’ knowledge levels regarding the benefits of butterfly pea flower after receiving education and to determine the effectiveness of this education in preventing stunting among toddlers in the working area of Kuta Baro Public Health Center, Aceh Besar. The research was conducted in the Kuta Baro Public Health Center area, Aceh Besar Regency, during Posyandu (integrated health post) activities from March to April 2025. The research design used was pre-experimental with a one-group pretest–posttest approach. The sample consisted of 99 parents of stunted toddlers, selected using a total sampling technique. The research instrument was a knowledge questionnaire administered before and after the educational intervention using poster media. Statistical analysis using a paired t-test showed an increase in the average knowledge score from 36.89 to 37.76 with a p-value of 0.040 (<0.05), indicating a significant difference between pretest and posttest results. These findings demonstrate that education about butterfly pea flower significantly improves parents’ knowledge and has potential as an educational intervention for stunting prevention. In conclusion, education on the benefits of butterfly pea flower proved effective in increasing knowledge, which serves as an essential foundation for behavioral change among parents in efforts to prevent stunting. It is recommended that future research explore the direct impact of butterfly pea flower consumption on nutritional status or child growth indicators, not merely on knowledge aspects.